A Suicide Attempt Multicomponent Intervention Treatment (SAMIT Program): study protocol for a multicentric randomised controlled trial - Beneria, Anna; Motger-Albertí, Anna; Quesada-Franco, Marta; Arteaga-Henríquez, Gara; Santesteban-Echarri, Olga; Ibáñez, Pol; Parramon-Puig, Gemma; Sanz-Correcher, Pedro; Galynker, Igor; Ramos-Quiroga, Josep Antoni; Pintor, Luis; Bruguera, Pol; et al. (BMC psychiatry, 2024)
Suicide has become a first-order public health concern, especially following the negative impact of COVID-19 on the mental health of the general population. Few studies have analysed the effects of early psychotherapeutic interventions on subjects who have attempted suicide, and even fewer have focused on those hospitalized in non-psychiatric units after a Medically Serious Suicide Attempt (MSSA). The main aim of this study is to describe the protocol designed to evaluate the effectiveness of individual psychological treatment for patients hospitalized after an MSSA. The secondary objectives of the study are: (1) to evaluate the impact on quality of life and other psychosocial variables of patients with a recent MSSA who receive early psychological intervention; (2) to analyse the biological, psychological, and clinical impact of early psychotherapeutic treatment on subjects hospitalized after an MSSA. A longitudinal randomised controlled trial will be conducted with patients over 16 years of age admitted to two general hospitals. The case intervention group will enrol for 8-sessions of individual psychotherapy, Suicide Attempts Multi-component Intervention Treatment (SAMIT), combining Dialectical Behaviour Therapy (DBT), Mentalization-Based Therapy (MBT), and Narrative approaches, while the control group will receive a treatment-as-usual intervention (TAU). Longitudinal assessment will be conducted at baseline (before treatment), post-treatment, and 3, 6, and 12 months after. The main outcome variable will be re-attempting suicide during follow-up. Some psychotherapeutic interventions, usually implemented in outpatient, have proven to be effective in preventing suicidal behaviours. The combination of some of these may be a powerful treatment for preventing future SA in patients hospitalised after an MSSA, which is the most severely suicidal subgroup. Moreover, assessment of the biological, clinical and psychometric impact of this new intervention on patients during the first year after the attempt may help understand some of the multi-level factors associated with the effectiveness of psychotherapeutic interventions in MSSAs. The prevalence of high suicide rates requires the design of effective psychological interventions for their prevention, and also in order to design new pharmacological and psychological treatments. ClinicalTrials.gov ID: NCT06238414. Date of registration: 1st February 2024, final update is protocol version 3.0, 19th March 2024.